2019
DOI: 10.1108/bfj-09-2018-0617
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dining experience on future intention in quick service restaurants

Abstract: Purpose The purpose of this paper is to examine the effect of the dining experience including food quality, service quality, convenience and ambiance on overall satisfaction and customers’ intention to revisit in quick service restaurants (QSRs). In addition, the mediating effects of overall satisfaction between dining experience dimensions and customer intention to revisit have been investigated in this study. Design/methodology/approach Data were collected online from 278 participants in the USA and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 84 publications
(70 reference statements)
4
32
0
9
Order By: Relevance
“…A number of studies highlighted the applicability of SERVQUAL instruments such as DINESERV (Stevens et al , 1995), DINESCAPE (Ryu and Jang, 2008) or TANGSERV (Raajpoot, 2002) for foodservices. All these instruments capture different dimensions of quality and differ according to whether they are full service (Park and Jang, 2014a; Ryu et al , 2012; Jani and Han, 2011) or quick service (Nguyen et al , 2018; Etemad-Sajadi and Rizzuto, 2013; Richardson et al , 2019). Depending on the research focus, research highlighted either the importance of staff-related SQ, food quality or environmental factors such as ambiance.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…A number of studies highlighted the applicability of SERVQUAL instruments such as DINESERV (Stevens et al , 1995), DINESCAPE (Ryu and Jang, 2008) or TANGSERV (Raajpoot, 2002) for foodservices. All these instruments capture different dimensions of quality and differ according to whether they are full service (Park and Jang, 2014a; Ryu et al , 2012; Jani and Han, 2011) or quick service (Nguyen et al , 2018; Etemad-Sajadi and Rizzuto, 2013; Richardson et al , 2019). Depending on the research focus, research highlighted either the importance of staff-related SQ, food quality or environmental factors such as ambiance.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…In our case, items in this dimension received the lowest mean scores from customers of a QSR in Barcelona, in line with Ryu and Jang's (2008) finding that the physical environment is less important in QSRs than in upscale ones. Richardson et al (2019) did not identify a statistically significant relationship between ambience and customer satisfaction in QSRs either. However, according to Tsai et al (2007), store appearance is an important factor for the analysis of service quality in fast food chains, and our study supports this claim.…”
Section: Discussion Of the Findingsmentioning
confidence: 60%
“…Nam et al (2011) found a positive influence of service quality on customer satisfaction and brand loyalty in hotel and restaurant customers in the United Kingdom. In the same vein, Bujisic et al (2014) and Richardson et al (2019) observed a positive influence of service quality on overall satisfaction and future intentions among QSR customers. Finally, Qin and Prybutok (2008) asserted that service quality assessment provides decisive information to improve business performance and strategic positioning in the marketplace.…”
Section: Literature Review 21 Service Quality Benefitsmentioning
confidence: 76%
“…As proposed in this study, destination servicescape quality (DSQ) comprises twodimensional concepts, hard-servicescape, and soft-servicescape, describing all tangible attributes of a destination and intangible social attributes, indicated by the ease of getting and affording an accommodation-hotel and restaurant (Richardson, Lefrid, Jahani, Munyon, & Rasoolimanesh, 2019). Another hard-servicescape is the attractiveness of events and destination-related activities (Akroush et al, 2016;Alazaizeh et al, 2016).…”
Section: Destination Servicescape Quality and Authentic Value Advantage In The Sdl Perspectivementioning
confidence: 99%